Optimization of Hydraulic Fracturing Modeling on The Proppant Flowback Issue Well DF-007 - Nugraha, Fanata Yudha; Cahyaningtyas, Ndaru; Addin, Dhaffa Izuddin; Tony, Brian; Nandiwardhana, Damar (Journal of Earth Energy Science, Engineering, and Technology, 2025)
Well DF-007, Field IA, Talang Akar Formation has low permeability that hinders well productivity. To improve production performance, hydraulic fracturing operations need to be conducted on the well. However, after the operation, a proppant flowback problem was discovered when the well was put back into production. This issue disrupts production performance and causes proppant accumulation. This problem indicates the need for a comprehensive analysis of the factors leading to proppant flowback issues, before determining a solution that addresses the root cause of the problem. The research flow begins with analyzing the factors causing proppant flowback issues such as initial production management settings, mechanical, and hydrodynamic force factors. After identifying the main issue, which is the hydrodynamic force factor, the process continues to the re-modeling stage by selecting proppants and fracturing fluids. The solution is determined by selecting the YF135.1HTD fracturing fluid with high viscosity to optimize proppant transportation, as well as choosing a combination of conventional proppants and adding resin-coated or rod-shaped proppants in the final stage to strengthen the stability of the proppant layer. The evaluation results show that the use of a combination of the fracturing fluid YF135.1HTD and the proppants BorProp 16/20 (Ceramic) + 16/20 XRT Ceramax I (Resin Coated Ceramic) can increase the average formation permeability from 5.33 mD to 181 mD, skin factor from +11.65 (damaged) to -6.03 (stimulated), fold of increase (FOI) of 8.21 times, as well as an increase in the gross rate on the inflow performance relationship (IPR) from previously 88 BFPD to 880 BFPD.